2019
DOI: 10.3390/ijerph16183336
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Emotional Disorders and Transportation Noise among Children and Adolescents: A Systematic Review and Meta-Analysis

Abstract: Children and adolescents may be particularly vulnerable to environmental influences such as noise which can affect mental well-being. The aim of this systematic review was to evaluate the effect of transportation noise on behavioral and emotional disorders in children and adolescents using a meta-analytic approach. Therefore, we searched four databases (Pubmed, Embase, PsychINFO, and PSYNDEX) and grey literature until February of 2019. We identified 14 articles from 10 studies examining the effect of transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 54 publications
(129 reference statements)
1
18
0
3
Order By: Relevance
“…For children and adolescents, a systematic review published whilst the current review was conducted [55] undertook a meta-analysis of three studies finding a harmful effect of road traffic noise on hyperactivity/inattention and total difficulties score of the Strengths and Difficulties Questionnaire [56] but no effect for conduct problems or emotional symptoms. The current review has concluded that there is low quality evidence for a harmful effect for emotional and conduct disorders, and hyperactivity, and very low-quality evidence for no effect for ADHD.…”
Section: Comparison Of the Systematic Review Findings Of The Review Umentioning
confidence: 99%
See 1 more Smart Citation
“…For children and adolescents, a systematic review published whilst the current review was conducted [55] undertook a meta-analysis of three studies finding a harmful effect of road traffic noise on hyperactivity/inattention and total difficulties score of the Strengths and Difficulties Questionnaire [56] but no effect for conduct problems or emotional symptoms. The current review has concluded that there is low quality evidence for a harmful effect for emotional and conduct disorders, and hyperactivity, and very low-quality evidence for no effect for ADHD.…”
Section: Comparison Of the Systematic Review Findings Of The Review Umentioning
confidence: 99%
“…However, the reviews differ in methodology, as Schubert et al, 2019 did not undertake the GRADE assessment but has the advantage of conducting meta-analyses albeit on a very small number of studies. All the reviews of the field of environmental noise effects on mental health identify the need for more studies that use similar outcomes and techniques [6,54,55,57]. At present, taken as a whole, the evidence suggests there are harmful effects of noise on mental health for children and adolescents: further studies will help to clarify whether this relationship holds for the wide variety of childhood mental health outcomes that have been investigated.…”
Section: Comparison Of the Systematic Review Findings Of The Review Umentioning
confidence: 99%
“…Lärminduzierte mentale und Verhaltensstörungen bei Kindern und Jugendlichen war ebenfalls Gegenstand einer aktuellen Metaanalyse und eines systematischen Übersichtsartikels [17,18]. Die Metaanalyse von 3 Querschnittstudien (n = 48 730) ergab eine OR von 1,11 (95 %-KI 1,04-1,19) für Hyperaktivität/Aufmerksamkeitsdefizit bzw.…”
Section: Lärmbelästigungunclassified
“…eine OR von 1,09 (95 %-KI 1,02-1,16) für die Summe der Verhaltensstörungen (z. B. emotionale Symptome, Hyperaktivität/Aufmerksamkeitsdefizit und Peerbeziehungsprobleme) pro Zunahme um 10 dB(A) L den durch Straßenverkehrslärm [17]. Allerdings konnte aufgrund der heterogenen Ergebnislage keine eindeutige Schlussfolgerung hinsichtlich der psychischen Auswirkungen wie Depression und Angst getroffen werden [18].…”
Section: Lärmbelästigungunclassified
“…Many risk factors for emotional disorders have been proposed from several different points of view. In this regard, a vast group of variables has been listed, including biological, temperamental, psycho-social, socio-contextual, and environmental ones [ 9 , 10 , 11 ]. The specific impact of these variables and their differential participation in predicting depression and anxiety disorders are still the subject of research controversies [ 11 ].…”
Section: Introductionmentioning
confidence: 99%